To perform the operation \(\sqrt{6} \times \sqrt{8}\), you can use the property of square roots that states \(\sqrt{a} \times \sqrt{b} = \sqrt{a \times b}\).
So, we have:
\[ \sqrt{6} \times \sqrt{8} = \sqrt{6 \times 8} \]
Calculating \(6 \times 8\):
\[ 6 \times 8 = 48 \]
Now, we have:
\[ \sqrt{6} \times \sqrt{8} = \sqrt{48} \]
Next, we need to simplify \(\sqrt{48}\). We can factor \(48\) into \(16\) and \(3\):
\[ 48 = 16 \times 3 \]
Now, we can simplify \(\sqrt{48}\):
\[ \sqrt{48} = \sqrt{16 \times 3} = \sqrt{16} \times \sqrt{3} = 4\sqrt{3} \]
So the final answer is:
\[ \sqrt{6} \times \sqrt{8} = 4\sqrt{3} \]